Impact of non‐pharmaceutical interventions for the COVID‐19 pandemic on emergency department patient trends in Japan: a retrospective analysis. Issue 1 (28th November 2020) - Sekine, Ichiro; Uojima, Haruki; Koyama, Hiroshi; Kamio, Tadashi; Sato, Morihiko; Yamamoto, Tadatsugu; Fukaguchi, Kiyomitsu; Fukui, Hiroyuki; Yamagami, Hiroshi
Abstract : Aim: The coronavirus disease (COVID‐19) pandemic massively impacted emergency department (ED) visits. The unavailability of specific therapies or vaccines has made non‐pharmaceutical interventions (NPIs) an alternative strategy for COVID‐19. We assessed the impact of NPIs (nationwide school closures and state of emergency) on ED visits during the COVID‐19 pandemic in Japan. Methods: This retrospective study compared the trends in ED visits from 1 January to 25 May, 2020 (during the pandemic) with the average during 2015–2019 (before the pandemic). The primary end‐point was the change in the number of ED visits during the COVID‐19 pandemic with those from before the pandemic, with the NPI application stratified across four periods in 2020: Period 0 (1–15 January), no COVID‐19 cases detected in Japan; Period I (16 January–1 March), initial COVID‐19 outbreak; Period II (2 March–15 April), nationwide school closures; Period III (16 April–25 May), state of emergency. Results: Compared with before the pandemic, the number of walk‐in ED visits significantly decreased by 23.1%, 12.4%, and 24.0% (4, 047 versus 3, 111; 3, 211 versus 2, 813; and 3, 384 versus 2, 573; P < 0.001 for all) in Periods I, II, and III, respectively. The number of ambulance ED visits during the pandemic significantly increased by 8.3% in Period I (1, 814 versus 1, 964, P = 0.002), whereas there was no significant change in Periods II and III with 2.7% and −3.1% (1, 547 versus 1, 589 and 1, 389 versus 1, 346; P = 0.335 and P = 0.284, respectively). Conclusions: The application of an NPI during the COVID‐19 pandemic could have significantly reduced patient attendance in the ED. Abstract : The Japanese government imposed a state of emergency and, consequently, the number of COVID‐19 patients and mortality rates have decreased. Compared with the pre‐pandemic period, the number of walk‐in ED visits during the pandemic period significantly decreased by 23.4% after the Japanese government declared a state of emergency.